2023
DOI: 10.1002/mco2.267
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic regulatory mechanisms of ferroptosis and its implications for biological processes and diseases

Abstract: Ferroptosis is a form of regulated cell death triggered by the iron‐dependent peroxidation of phospholipids. Interactions of iron and lipid metabolism factors jointly promote ferroptosis. Ferroptosis has been demonstrated to be involved in the development of various diseases, such as tumors and degenerative diseases (e.g., aortic dissection), and targeting ferroptosis is expected to be an effective strategy for the treatment of these diseases. Recent studies have shown that the regulation of ferroptosis is aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 203 publications
0
9
0
Order By: Relevance
“…Consistently, previous studies observed upregulation of ferroptosis in ATAAD marked by overexpression of several FRGs including SLC7A11 and FSP1 and the downregulation of GPX4 [ 47 , 48 ]. In addition, targeting at ferroptosis might have the potential value in the alleviation of aortic dissection [ 47 , 49 ]. These studies supported that ferroptosis might participate in the pathogenesis of aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, previous studies observed upregulation of ferroptosis in ATAAD marked by overexpression of several FRGs including SLC7A11 and FSP1 and the downregulation of GPX4 [ 47 , 48 ]. In addition, targeting at ferroptosis might have the potential value in the alleviation of aortic dissection [ 47 , 49 ]. These studies supported that ferroptosis might participate in the pathogenesis of aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the methylation modification of DNA is mediated by DNA methyltransferases (DNMTs), such as DNMT1, DNMT3A, and DNMT3B. This modification generally has a negative effect on gene expression [49,50].…”
Section: Dna Methylation Regulates Ferroptosismentioning
confidence: 99%
“…The role of ferroptosis in pathological cell death associated with degenerative diseases, carcinogenesis, stroke, intracerebral hemorrhage, traumatic brain injury, ischemia–reperfusion injury, and kidney degeneration is increasingly being recognized [ 10 , 858 – 861 ]. Moreover, the potential of ferroptosis as a tumor-suppressor function that could be harnessed for cancer therapy is an exciting development.…”
Section: Conclusion and Perspectivementioning
confidence: 99%